Composite Action in the Reinforced Concrete Beam - UPPAL, ABDUL SHAKOOR (My University, 1969)
This thesis involves the treatment of the reinforced concrete beam as a composite beam with incomplete interaction. Influence of the loss of interaction and other parameters on the flexural cracking, and the moment capacity of the remaining uncracked portion of the reinforced concrete beam is studied analytically.
Keywords: Engineering